Modification and Characterization of Biodegradable Chitosan/ Starch-Based Films with Monomer 1,4-Butanediol Diacrylate (BDDA) by Gamma Radiation - Akter, Nousin; Saha, Suvanker; Hossain, Farah M.J.; Quader, Fahad B.; Alamgir, Poonam; Khan, Ruhul A. (Journal of Research Updates in Polymer Science, 2013)
Chitosan reinforced starch-based biodegradable films were prepared by solution casting. Tensile strength (TS), tensile modulus (TM), elongation at break (%), and water vapor permeability (WVP) of the 50% chitosan containing starch-based films were found to be 47 MPa, 550 MPa, 16%, and 2.45 g·mm/m2·day·kPa, respectively. Monomer 1,4 butanediol diacrylate (BDDA) was added (0.25-1% by wt) to the starch/chitosan (50:50) based film formulation. Then, films were cast and gamma irradiated from a radiation dose varied from 1 kGy to 25 kGy. Then mechanical and barrier properties were evaluated. The highest TS (80 MPa) and TM (880 MPa) of the films were found by using 0.5% monomer at 5 kGy dose. The WVP of the films were found to be 1.50 g·mm/m2·day·kPa which is 38.77% lower than control starch/chitosan-based films. Molecular interactions due to incorporation of BDDA were supported by Fourier transform infra red (FTIR) spectroscopy. The water uptake of the films pointed out better hydrophobic character due to incorporation of BDDA in starch/chitosan-based films. Surface morphologies of BDDA treated films were examined by scanning electron microscope (SEM) and suggested better morphologies due to BDDA treatment with starch/chitosan-based biodegradable films.